2013
DOI: 10.1186/1749-8090-8-218
|View full text |Cite
|
Sign up to set email alerts
|

Impact of epicardial ablation of concomitant atrial fibrillation on atrial natriuretic peptide levels and atrial function in 6 months follow-up: does preoperative ANP level predict outcome of ablation?

Abstract: BackgroundEpicardial ablation concomitant to cardiac surgery is an easy and safe approach to treat atrial fibrillation (AF), but its efficacy in longstanding persistent (LsPe) AF remains intermediate. Although larger left atrial size has been associated with worse outcome after ablation, biochemical predictors of success are not well established. The aim of this study was to evaluate relationship between biochemical marker, echo-characteristic and cardiac rhythm in 6 months follow-up after epicardial ultrasoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…At 3 and 6 months remained in SR 66.7% and 100% of patients with paroxysmal AF, 100% and 90% of patients with persistent AF and 33.3% and 56% of patients with permanent AF. As predictors of the ablation outcome, Pizón found that patients who maintained sinus SR had a smaller left atrial diameter and a smaller left atrial area [32]. In our study, the variables that were related to maintenance of SR at first year were Euroscore and the size of left atrium in the univariate analysis, while in multivariate analysis were paraxismal AF, age and male gender.…”
Section: Discussionmentioning
confidence: 54%
“…At 3 and 6 months remained in SR 66.7% and 100% of patients with paroxysmal AF, 100% and 90% of patients with persistent AF and 33.3% and 56% of patients with permanent AF. As predictors of the ablation outcome, Pizón found that patients who maintained sinus SR had a smaller left atrial diameter and a smaller left atrial area [32]. In our study, the variables that were related to maintenance of SR at first year were Euroscore and the size of left atrium in the univariate analysis, while in multivariate analysis were paraxismal AF, age and male gender.…”
Section: Discussionmentioning
confidence: 54%
“…An interesting finding that emerged from the studies is the kinetics of ANP after catheter ablation. These data [ 48 ] showed that there was a transient increase in ANP levels shortly after the procedure that gradually decreased thereafter. These observations suggest that direct damage to atrial cells releases more ANP.…”
Section: The Role Of Anp In Atrial Fibrillationmentioning
confidence: 99%
“…A study by Nakanishi et al [ 49 ] suggests that in patients with AF, undergoing catheter ablation, increased ANP levels are associated with favorable atrial remodeling. Similarly, a study of epicardial AF ablation [ 48 ] showed that in patients with long-standing persistent AF, increased ANP levels were associated with persistence of the sinus rhythm despite a low success rate. Conversely, a meta-analysis [ 50 ] showed that higher ANP levels were an independent predictor of AF recurrence, but only in patients without structural heart disease.…”
Section: The Role Of Anp In Atrial Fibrillationmentioning
confidence: 99%